The relationship between digital game addiction, reading motivation and students' comprehension levels - Kaman, Şafak; Bulut, Aydın (e-Kafkas Egitim Arastirmalari Dergisi, 2025)
This research aimed to determine the relationship between digital game addiction, reading comprehension, and reading motivation among fourth-grade elementary school students. The study aims to identify the extent to which the level of digital game addiction in children affects their reading skills. The research was designed as a correlational scanning study. The sample group of the study consisted of 374 fourth-grade students attending schools in the Pursaklar district of Ankara during the 2023-2024 academic year. The data collection instruments used were the Digital Game Addiction Scale, Reading Comprehension Test, and Reading Motivation Scale. SPSS package program was used for data analysis, and Pearson Moment Correlation Coefficient, t-test, mean, and percentage were used in the analysis of the findings. It was found that there is a moderately negative relationship between digital game addiction and reading motivation, a moderately significant negative relationship between digital game addiction and reading comprehension, and a moderately significant positive relationship between reading motivation and reading comprehension. Additionally, it was concluded that the digital game addiction of male students is higher than that of female students; however, female students have higher levels of reading motivation and reading comprehension compared to male students. The research findings indicate that as digital game addiction increases, students' motivation to read and their reading comprehension skills decrease. It was observed that the addiction of children to games they enjoy playing negatively affects their reading skills.